Impact of Structured Postoperative Surveillance on Survival in Patients with Resected Pancreatic Adenocarcinoma - Jacobsen, Anne; Flessa, Maarten; Abels, Anna-Lena; Czubayko, Franziska; Mittelstädt, Anke; Krautz, Christian; Weber, Georg; Grützmann, Robert; Brunner, Maximilian (Cancers, 2025)
Background: This study aimed to investigate whether structured surveillance after resection of PDAC has an impact on survival. Methods: 206 patients who underwent PDAC resection at the University Hospital Erlangen between 2005 and 2020 and survived for at least 90 days postoperatively were included in this retrospective study. The impact of surveillance (structured vs. no structured surveillance) respectively of recurrence patterns (recurrence in follow-up vs. symptomatic recurrence) on overall and disease-free survival was investigated. Results: A total of 157 patients (76%) participated in a structured surveillance program after pancreatic resection. During a mean follow-up of 28.5 months, 137 patients (67%) developed recurrence. Patients with structured surveillance showed significantly better outcomes for overall survival after surgery (OSaS: 29.2 months with structured surveillance vs. 16.4 months without, p < 0.001), overall survival after recurrence (OSaR: 10.8 months vs. 3.6 months, p < 0.001), and disease-free survival (DFS: 14.8 months vs. 11.4 months, p = 0.010). In a subgroup analysis of 112 patients with recurrence, survival benefits were observed for those whose recurrence was detected during follow-up compared to those with symptomatic recurrence (OSaS: 24.8 months in the follow-up group vs. 17.2 months in the symptomatic group, p < 0.001; OSaR: 12.6 months vs. 6.5 months, p < 0.001). Conclusion: This study provides evidence that structured surveillance after PDAC resection is beneficial for both overall and disease-free survival. However, randomized studies are needed to confirm the positive impact of structured surveillance programs on survival after pancreatic resection.
CRIS-Team Scopus Importer:2025-05-23
Keywords: follow-up; pancreatic cancer; pancreatic ductal adenocarcinoma; recurrence; surveillance